New onset diabetes, type 1 diabetes and COVID-19 - Boddu, Sirisha Kusuma (Diabetes Metab Syndr, 2020)
BACKGROUND AND AIMS: New data has emerged regarding higher risk of coronavirus disease 2019 (COVID-19), and its severity and complications in patients with type 2 diabetes mellitus (T2DM). However, there is a dearth of evidence regarding type 1 diabetes mellitus (T1DM). This article explores the possibility of COVID 19 induced diabetes and highlights a potential bidirectional link between COVID 19 and T1DM. METHODS: A literature search was performed with Medline (PubMed), Scopus, and Google Scholar electronic databases till October 2020, using relevant keywords (COVID-19 induced diabetes; COVID-19 and type 1 diabetes; COVID-19 induced DKA; new-onset diabetes after SARS-CoV-2 infection) to extract relevant studies describing relationship between COVID-19 and T1DM. RESULTS: Past lessons and new data teach us that severe acute respiratory syndrome coronaviruses (SARS-CoV and SARS-CoV-2) can enter islet cells via angiotensin converting enzyme-2 (ACE-2) receptors and cause reversible β-cell damage and transient hyperglycemia. There have been postulations regarding the potential new-onset T1DM triggered by COVID-19. This article reviews the available evidence regarding the impact and interlink between COVID-19 and Τ1DM. We also explore the mechanisms behind the viral etiology of Τ1DM. CONCLUSIONS: SARS-CoV-2 can trigger severe diabetic ketoacidosis at presentation in individuals with new-onset diabetes. However, at present, there is no hard evidence that SARS-CoV-2 induces T1DM on it’s own accord. Long term follow-up of children and adults presenting with new-onset diabetes during this pandemic is required to fully understand the type of diabetes induced by COVID-19.